KLASIFIKASI DAN VOLUME KENDARAAN BINA MARGA DARI REKAMAN VIDEO LALULINTAS DENGAN METODE ARTIFICIAL INTELLIGENCE - YOLO V8 PADA JALAN TOL JAKARTA-BOGOR DAN JAKARTA-TANGERANG - Nur, Doni Haidar; Darmadi, Darmadi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The software helps solve things faster, e.g., Epanet software, Pipe Flow Expert, WaterCAD, SAP2000 planning software, etc. Likewise, in the field of calculating traffic volume with the development of artificial intelligence technology, using video recording, volume, and speed calculations can be done easily. At this time, the classification of traffic counting is only up to 3 (three) types of vehicles classified by YOLO V8, so in this research, the classification is added to be 6 (six) types of vehicles, namely mini cars, mobile passengers, small buses, big buses, small trucks, and large trucks, according to vehicle classification established in Indonesia. The research method is done by recording the traffic on the road and then video recording with the help of the software developed with the Python program so that the volume of the vehicle according to its classification is obtained. The result obtained from this research is compared to the manual traffic counting. The comparison between vehicle counting by the software and manual counting is mini-car 97.02%, passenger car 99.49%, small bus 96.94%, large bus 97.34%, small truck 93.21%, and large truck 97.18%.